A high-pressure crystallographic and magnetic study of Na5[Mn(l-tart)2]·12H2O (l-tart = l-tartrate). Issue 42 (8th October 2015) - Craig, Gavin A.; Woodall, Christopher H.; McKellar, Scott C.; Probert, Michael R.; Kamenev, Konstantin V.; Moggach, Stephen A.; Brechin, Euan K.; Parsons, Simon; Murrie, Mark
Abstract : The crystal structure and magnetic properties of the compound Na5 [Mn(l -tart)2 ]·12H2 O (1, l -tart =l -tartrate) have been investigated over the pressure range 0.34–3.49 GPa.1 retains its magnetic anisotropy even under pressure. Abstract : The crystal structure and magnetic properties of the compound Na5 [Mn(l -tart)2 ]·12H2 O (1, l -tart =l -tartrate) have been investigated over the pressure range 0.34–3.49 GPa. The bulk modulus of 1 has been determined as 23.9(6) GPa, with a compression of the coordination spheres around the Na + ions observed. 1 is therefore relatively incompressible, helping it to retain its magnetic anisotropy under pressure.